New Developments of the SimCLIM Model for Simulating Adaptation to Risks Arising from Climate Variability and Change - Warrick, Richard; Ye, W.; Hay, J.; Cheatham, C. (Modelling and Simulation Society of Australia and New Zealand Inc., 2005)
In terms of evaluating possible adaptations to climate change, one problem faced by decisionmakers is how to separate the risks from present, natural climatic variations and extremes from those associated with future greenhouse-gasinduced changes in climate. In particular, this separation is necessary in order to identify the “incremental costs” of adaptation associated with climate change. As reported here, this problem has been addressed by developing an enhanced version of an integrated model system called SimCLIM. The SimCLIM system simulates, both temporally and spatially, the impacts of both climate variability and change. The model system has recently been expanded in ways that allow the topicof “incremental costs” of adaptation to be explored through simulation, with a particular focus on coastal risks. These improvements include: • open-framework system, which allows user access to import climate data and impact models for different areas and resolutions; • sea-level scenario generator, which includes the capacity for including regional and local components of sealevel change; • land use scenario generator that allows the user to examine the implications for vulnerability under assumptions about different pathways and controls on future growth and development; • capacity for transient simulations that complements the “time-slice” approach to impact assessment and allows for timedependent changes in climate and land use and their effects to be analysed; • explicit capacity for examining adaptation options, including outputs that allow comparisons of simulations with and without climate change; • economic tools for evaluation of impacts and adaptation options, specifically focussing on economic costs and benefits. This paper describes these improvements to SimCLIM and demonstrates their application through a pilot study of coastal flood risk from tropical cyclones in a community on the island of Rarotonga, Cook Islands. Multiple simulations are conducted with and without climate change, and with and without adaptation. The results thereby give clear indications of the relative magnitude of present and future impacts of tropical cyclones and the relative costs and benefits of adaptation options for reducing the risks.